Circulating long noncoding RNA PDE4DIPP6: a novel biomarker for improving the clinical management of non-ST-segment elevation myocardial infarction - Koch, Pia-Franziska; García-Hidalgo, María C.; Labus, Josephine; Biener, Moritz; Thum, Thomas; Gonzalo-Calvo, David de; Bär, Christian (Clinica chimica acta, 2024)
Background - Long noncoding RNAs (lncRNAs) have emerged as promising diagnostic biomarkers. Here, we investigated the cardiac-expressed and plasma-detectable lncRNA PDE4DIPP6 as a biomarker for non-ST-segment elevation myocardial infarction (NSTEMI), specifically assessing its potential to enhance the diagnostic efficacy of high-sensitivity cardiac troponin (hs-cTnT). - Methods and Results - The study enrolled individuals presenting with suspected acute coronary syndrome (ACS). LncRNA quantification was performed in plasma samples using RT-qPCR. The discriminatory performance was assessed by calculating the Area Under the Curve (AUC). Reclassification metrics, including the Integrated Discrimination Improvement (IDI) and Net Reclassification Improvement (NRI) indexes, were utilized to evaluate enhancements in diagnostic accuracy. Among the 252 patients with suspected ACS, 50.8 % were diagnosed with ACS, and 13.9 % with NSTEMI. Initially, the association of lncRNA PDE4DIPP6 with ACS was investigated. Elevated levels of this lncRNA were observed in ACS patients compared to non-ACS subjects. No association was found between lncRNA PDE4DIPP6 levels and potential confounding factors, nor was a significant correlation with hs-cTnT levels (rho = 0.071). The inclusion of lncRNA PDE4DIPP6 on top of hs-cTnT significantly improved the discrimination and classification of ACS patients, as reflected by an enhanced AUC of 0.734, an IDI of 0.066 and NRI of 0.471. Subsequently, the lncRNA PDE4DIPP6 was evaluated as biomarker of NSTEMI. Elevated levels of the lncRNA were observed in NSTEMI patients compared to patients without NSTEMI. Consistent with previous findings, the addition of lncRNA PDE4DIPP6 to hs-cTnT improved the discrimination and classification of patients, increasing the AUC from 0.859 to 0.944, with an IDI of 0.237 and NRI of 0.658. - Conclusion - LncRNA PDE4DIPP6 offers additional diagnostic insights beyond hs-cTnT, suggesting its potential to improve the clinical management of patients with NSTEMI.
Online verfügbar: 29. Juni 2024, Artikelversion: 5. Juli 2024
Gesehen am 03.02.2025